The forming of ethnic and cultural information space of the Republic of Sakha (Yakutia) (Herald of Journalism, 2016)
This article considers the independent printed press and the forming of ethnic and cultural information space of the Republic of Sakha (Yakutia), Russian Federation in 1990-1991. The author uses content analysis of such publications as the «Tuscul» (Tuskul - Future) newspaper and the ILIN (Ilin - The East) magazine. The public activity, the ability to create their own publications, publicity, freedom of speech and the creation of «Sakha Omuk» (Sakha Nation; the Union of non-governmental organisations and yakutpeople) had a significant impact on the ethnic and cultural information space.
Keywords: Yakutia; ethno-cultural; identity; information space; transparency; freedom of speech; 1990s; the Tuscul newspaper; the ILIN magazine; Sakha Omuk